Analisis Studi Kelayakan Bisnis Pada Usaha UMKM Ayam Geprek Crunchy Sawah Lebar Kota Bengkulu : Tinjauan Aspek Legalitas, Sistem Pemasaran, Dan Keuangan - Astuty, Kamelia; Vera, Nirta; Yanti, Rina Trisna; Paramita, Tesi (Jurnal Dehasen Mengabdi, 2025)
Improving the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in the digital era is one of the important challenges in supporting economic growth. In analyzing the business feasibility study of the Ayam Geprek Crunchy MSME business in Sawah Lebar, Bengkulu City, focusing on three main aspects: legality, marketing system, and finance. A business feasibility study is essential to ensure that the business is not only financially viable, but also fulfills legal aspects and has an effective marketing strategy. From the legality aspect, the study highlights the importance of having licensing documents such as a Trade Business License (SIUP), Taxpayer Identification Number (NPWP), and halal certification that can increase consumer confidence and facilitate access to capital. In the marketing aspect, the Ayam Geprek Crunchy business utilizes direct marketing, social media, and delivery services to expand market reach, as well as segmenting and targeting consumers appropriately to increase competitiveness in the midst of intense market competition. From a financial perspective, the analysis shows that the geprek chicken business has a large enough profit margin, relatively low operating costs, and high sales potential, making it possible to reach the break-even point in a short time and providing promising profit prospects. The results of this study conclude that the Ayam Geprek Crunchy business in is feasible to run, with a note of the need for risk management and sustainable business development strategies.